Education Policies in Venezuela (2000-2016): A Critical View (2019)
The purpose of this study is to present a critical view of the educational policies implemented by the Venezuelan State during the government of President Hugo Chávez Frías (1999-2012) and continued by President NicolásMaduro (2013-2016) within the so-called "Bolivarian Revolution" and the "Socialism of the 21st Century".   In this sense, we have approached the study of this political-educational process from the perspectives of the Social History of Education, which leads us to situate education in its global social context, since 1948, in the historical time of the implementation of the model of Mass Education in which the 1999 Constitution is inscribed and from which it guides the design of public policies in the education sector during 1999-2016.  In order to facilitate the reader's understanding of this process, we have divided this essay into two parts: The first briefly reconstructs the educational process from 1948 to 2010, while the second part focuses on the evaluation of education policies at the university level, especially with regard to their impact on one of the missions of the University; the scientific research and the production of knowledge.